Penerapan Etika dalam Manajemen Pendidikan Islam (Studi Kasus pada Lembaga di MTs NW Selebung Ketangga) - Alparizi, Ahmad Salman (ALSYS, 2025)
Building character and educational ethics through everyday interactions, particularly within family and societal contexts, constitutes a primary objective of Islamic Religious Education. This study aims to explore the application of ethics, the principal's role, and the challenges in managing Islamic education at MTs NW Selebung Ketangga. Employing a qualitative descriptive research design, data collection techniques included participant observation, interviews, and documentation. The research subjects comprised the principal, teachers, and students, providing a comprehensive view of the ethical framework within the institution. The findings reveal that the implementation of ethical activities in Islamic education management, along with exemplary behavior demonstrated by teachers, positively influences student conduct. These results indicate that MTs NW Selebung Ketangga effectively enhances student ethics through structured educational practices and role modeling. The study contributes to the understanding of ethical education in Islamic contexts and highlights the importance of leadership and community involvement in fostering a values-based educational environment.